The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.fishres.2006.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the effect of round straps on the selectivity in a diamond mesh cod-end

Abstract: FEMNET, a numerical tool based on the finite element method, was applied to estimate the shapes of various diamond-mesh cod-end designs during fishing. The only design differences rest in the use of round straps of different lengths, positions and numbers. The cod-end shape estimates were then entered in the selectivity simulation tool PRESEMO to simulate the selectivity processes of the various cod-end designs under the same varying fishing conditions. This enabled us to demonstrate how one or two round strap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The design guides demonstrate the importance of mesh OAs during fishing. This effect of OA demonstrates that technical measures such as codend round-straps and lastridge ropes can affect L50 value because they restrict the codend meshes or help them open as the catch builds up during the fishing process (Herrmann et al 2006). For diamond mesh codends, the OA value is not completely fixed, as it can vary with location along the codend (Herrmann et al 2007) and is affected by the amount of catch (Herrmann 2005a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The design guides demonstrate the importance of mesh OAs during fishing. This effect of OA demonstrates that technical measures such as codend round-straps and lastridge ropes can affect L50 value because they restrict the codend meshes or help them open as the catch builds up during the fishing process (Herrmann et al 2006). For diamond mesh codends, the OA value is not completely fixed, as it can vary with location along the codend (Herrmann et al 2007) and is affected by the amount of catch (Herrmann 2005a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Simulating the selective potential of the diamond-mesh cod end based on fish morphology.-Several studies have demonstrated that not only mesh size but also the openness of the meshes in diamond-mesh cod ends affects net selectivity (Herrmann 2005a(Herrmann , 2005bHerrmann and O'Neill 2005;Herrmann et al 2007;O'Neill and Herrmann 2007;Herrmann et al 2009). During trawling, the cod end meshes are stretched by hydrodynamic drag forces that act primarily on the accumulated catch in the aft end of the cod end (Herrmann 2005b;Herrmann et al 2006), where the mesh opening is unlikely to exceed 75 degrees. The same mesh state can be expected during the closing phase of the Danish seine fishing process, when the diamond-mesh netting is stretched and under tension due to pulling by the seine ropes.…”
Section: Methodsmentioning
confidence: 99%
“…Roundstraps are known to affect selectivity of codends (Herrmann et al 2006). Because the codends were used in commercial activity, both codends had 24 mm diameter Danline round straps of ca.…”
Section: Sea Trialsmentioning
confidence: 99%